2013
DOI: 10.1007/s11255-013-0381-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microscopic (pT3a) and gross extravesical extension (pT3b) in pathological staging of bladder cancer: analysis of patient outcomes

Abstract: Macroscopic extravesical extension (pT3b) is not associated with a worse outcome than pT3a disease in lymph node-negative cases of bladder urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
3
4
1
Order By: Relevance
“…examined 236 patients (median follow‐up = 8.9 years) with pT3 urinary bladder cancer and found no significant difference in recurrence or survival rates between patients with pT3a and pT3b tumours; lymph node and surgical margin status were the only factors to impact patient prognosis significantly among pT3 patients. Other studies have also demonstrated similar findings . Conversely, several recent, large studies have found that pT3b is associated with worse outcome compared to pT3a .…”
Section: Stage Pt3 Carcinomasupporting
confidence: 52%
See 1 more Smart Citation
“…examined 236 patients (median follow‐up = 8.9 years) with pT3 urinary bladder cancer and found no significant difference in recurrence or survival rates between patients with pT3a and pT3b tumours; lymph node and surgical margin status were the only factors to impact patient prognosis significantly among pT3 patients. Other studies have also demonstrated similar findings . Conversely, several recent, large studies have found that pT3b is associated with worse outcome compared to pT3a .…”
Section: Stage Pt3 Carcinomasupporting
confidence: 52%
“…Other studies have also demonstrated similar findings. 100,117,118 Conversely, several recent, large studies have found that pT3b is associated with worse outcome compared to pT3a. [112][113][114]119 For example, Tilki et al 120 included 808 patients who underwent radical cystectomy with stage pT3 and found that although there was no significant difference overall in outcome of pT3a versus pT3b patients, of the patients without lymph node metastasis (pN0) pT3b was associated with significantly worse 5-year recurrence-free survival (47.9 versus 60.7%) and cancerspecific survival (55.0 versus 64.4%) compared to pT3apN0 patients.…”
Section: Stage Pt3 Carcinomamentioning
confidence: 99%
“…In order to diminish the potential bias of LNI, we calculated the same models after excluding all patients with positive lymph nodes (n = 50) using multivariable Cox regression models. Similar to previous studies addressing this issue [5,7,8], pT3 substage in our node-negative cohort of 66 patients had no independent impact on survival (data not shown). …”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, several authors presented their findings addressing the prognostic impact of pT3a versus pT3b tumors [5,6,7,8,9,10,11]. However, data addressing this issue is far from conclusive and still under debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation